Migration, ethnicity, racism and the COVID-19 pandemic: A conference marking the launch of a new Global Society - Laurence Gruer; Charles Agyemang; Raj Bhopal; Antonio Chiarenza; Allan Krasnik; Bernadette Kumar (Elsevier, 2021)
The inaugural conference of the Global Society on Migration, Ethnicity, Race and Health COVID-19 examined the impact of the COVID-19 pandemic on migrants and ethnic minorities and the role of racism. Migrants everywhere have faced tightening immigration restrictions, more obstacles to healthcare, increased racism and worsening poverty. Higher COVID-19 mortality rates have been otbserved in ethnic/racial minorities in the United Kingdom and the United States. Structural racism has been implicated, operating, for example, through more crowded living conditions and higher-risk occupations. In Brazil, good data are lacking but a seroprevalence survey suggested higher rates of infection among ethnic minorities and slum dwellers. Considerable disruption of services for migrants at the border with Venezuela have occurred. National policy responses to protect vulnerable groups have been lacking. In Australia, with strict COVID-19 control metrtrun 0asures and inclusive policies, there have been few cases and deaths reported in Indigenous communities so far. In most countries, the lack of COVID-19 data by ethnic/racial group or migrant status should be addressed. Otherwise, racism and consequent inequalities will go undetected.